PENANGANAN KELUHAN, KELENGKAPAN FASILITAS DAN GOLONGAN LAYANAN PESERTA SEBAGAI FAKTOR PENENTU KEPUASAN PESERTA ASKES SOSIAL PADA PT. ASKES CABANG BANYUMAS DI ASKES CENTER RSU BANYUMAS - Herni Utami Rahmawati; Heri Susilo Widodo (Pro Bisnis, 2011)
The research takes the title of ,.The handling of complaint, completeness of facikty, and the service group of heatth insurence .i-f,n^ ai the main factor of thL health insurance social members in pr. aSKES of Banyumas at health"insuranle of laulymas Public Hospital". The goar of this research is for analyzing the impact if handling of complaint, completeness of facility, and tie service gyoup of h"aM insurance members toward the satisfaction of heakh insurance *"ib"ri, ai well as to measure the level of their satisfaction. Related to the problem, this research uses hypotheses. First is the handling of complaint which hai the positive impact toward the health insurance members satisfaction. second is the cimpletenesi to"itiry not the positive impact for health insurance members satisfaction. Third is' the simice group of health insurance members has the positive impact for heahh insurancemembers satisfaction. And the fourth is the level of heatih insurance members whoare ofiicial servant is not more than 83%. As the result of analysis, it can beconc.luded that the handling of complaint has positive and signiJicani impact towardthe health insurance members satisfaction in public hospitil o7 noryui^ becausethe sig value 0.000 < 0.05. The completeness focility has positive impact toward thehealth iwurance members satisfaction with the sig value of 0.000 < 0.05. The servicegroup of healt insurance members has the positive impact toward their satisfactionwith the sig value of 0.038 < 0.05. The level of the health insurence memberssatisfaction who are oficial servant is not more than 83o%. From the conclusion, wecan state that we are able to the increase the health insurance members satisfactionas the corporation's mission, so the corporation should give the best service, that isnever different the handling of complaint as the health insurance service for healthinsurance members according to their group